External Flow Field Simulation of Low Ambient Temperature Air-source Heat Pump Array - Tan Qingpeng; Liu Jinping; Chen Jianxun; Chen Xiao; Chen Ziyu (Zhileng xuebao)
In this study, physical models of six-row and four-row arrays of a low-ambient-temperature air-source heat pump with and without wall obstruction are established. A three-dimensional numerical simulation of the ambient flow field of the low-ambient-temperature air-source heat pump under nominal working conditions at 261.15 K is carried out. In this study, the inlet air temperature of the evaporator surface and the heat transfer rate of the low-ambient-temperature air-source heat pump under different horizontal wind speeds are investigated. The location of the unit under the worst conditions is determined, and the influence of cold air backflow on the heat transfer performance is analyzed. The ambient wind hindered the diffusion of cold air at the fan outlet and increased the deflection angle of the fan outlet, resulting in the accumulation of cold air in the upper part of the fan, and the cold air reflux phenomenon in the unit was more obvious inside and on the lee side the array. The results showed that when the horizontal distance between the units was 0.6 m, the horizontal wind speed increased from 0 to 5 m/s. The lowest inlet air temperature of the array unit is 2.44–3.69 K lower than the ambient temperature; the average heat transfer decreases by 1%–6.2%, and the average inlet air temperature is 0.78–1.57 K lower than the ambient temperature. When the distance between the unit and wall is 0.6 m, the horizontal wind speed increases from 0 m/s to 5 m/s, respectively; the lowest inlet air temperature of the array unit is 3.51–4.14 K lower than the ambient temperature; the average heat transfer rate decreases by 5.9%–11.5%, and the average inlet air temperature is 1.29–1.98 K lower than the ambient temperature. On this basis, an array air-source heat pump was simulated under different lateral spacings and distances from the wall. The results showed that increasing the lateral spacing or distance from the wall enhanced the heat transfer of the array low-ambient-temperature air-source heat pump unit. When the lateral spacing increases to 1.8 m, the average heat transfer rate of the array unit can reach more than 96.5% of the baseline heat transfer rate of the array unit. When the distance from the wall is increased to 1.8 m, the average heat transfer rate of the array unit can be more than 91.3% that of the baseline unit. A horizontal spacing or a spacing from the wall of 1.2 m is a better installation spacing, which provides a theoretical basis for on-site installation.